N-acyl dopamine derivates as lead compound for implementation in transplantation medicine - Wedel, Johannes; Yard, Benito A. (Transplantation reviews, 2015)
Conjugates of fatty acids with ethanolamine, amino acids or monoamine neurotransmitters occur widely in nature giving rise to so-called endocannabinoids. Anandamide and 2-arachidonoyl glycerol are the best characterized endocannabinoids activating both cannabinoid receptors (CB1 and CB2) and transient receptor potential vanilloid type 1 (TRPV1) channels (anandamide) or activating cannabinoid receptors only (2-arachidonoyl glycerol). TRPV1 is also activated by vanilloids, such as capsaicin, and endogenous neurolipins, e.g. N-arachidonoyl dopamine (NADA) and N-oleoyl dopamine (OLDA). Because donor dopamine treatment has shown to improve transplantation outcome in renal and heart recipients, this review will mainly focus on the biological activities of N-acyl dopamine derivates (NADD) as potential non-hemodynamic alternative for implementation in transplantation medicine. Hence the influence of NADD on transplantation relevant entities, i.e. cold inflicted injury, cytoprotection, I/R-injury, immune-modulation and inflammation will be summarized. The cytoprotective properties of endogenous endocannabinoids in this context will be briefly touched upon.
Gesehen am 15.03.2018